Investigating the Level of Nurses’ Empathy in the Workplace in Kawsar Hospital in Sanandaj City in 2022: Cross Sectional Study - Serveh Mafakheri; Bahre Shakeri; Mohammad Azad Majedi; Yousef Moradi; Salam Vatandost (مجله دانشگاه علوم پزشکی جیرفت, 2024)
Introduction: Nurses are one of the important groups in the hospital. Considering the stressful conditions of the hospital environment, having appropriate empathy in nurses is of great importance. Therefore, the present study was conducted with the aim of determining the level of empathy of nurses in the work environment in Kawsar Hospital in Sanandaj city in 2022. Materials and Methods: The present study was conducted through a cross-sectional design in 2022 on nurses working in different departments of Kawsar Hospital in Sanandaj. 451 nurses were studied by census method. The data were collected using the standard questionnaires of demographic information, the interpersonal empathy, and the nurse-patient empathy by self-reporting and were analyzed by SPSS version 26. A significance level of 0.05 was considered. Results: The results showed that the overall score of nurses' interpersonal empathy and nurse's empathy with patients were 144.25±34.34, 64.11±8.34, respectively, which is in the middle range of the scores of the questionnaires. Also, the results of Pearson correlation test showed that there was a positive and significant correlation between the total score of nurses' interpersonal empathy and the total score of nurse-patient empathy. (r=0.456), (p<0/05). Conclusion: Considering the range of empathy scores, which both are at the average level, there is a need to improve it. Therefore, according to the positive consequences of the presence of empathy in the hospital environment, it is necessary to help improve the level of empathy in nurses as much as possible through academic training, in service training, and encouragement from authorities.